MEDIASI NON LITIGASI OLEH TOKOH MASYARAKAT PADA PERKARA POLIGAMI - Primastuti, Nur Fitria; Roikhatul Jannah; Nur Isna Fitriani; Zunaeni; Siti Zumrotun (USRAH: Jurnal Hukum Keluarga Islam, 2024)
This study aims to determine the effectiveness of the role of community leaders in non-litigation mediation of polygamy cases in Parakan District, Temanggung Regency. Non-litigation mediation is an alternative conflict resolution that is often faced by couples who want to practice polygamy, especially in the context of Islamic law and local socio-culture. Community leaders, including religious leaders and traditional leaders, play an important role as mediators in helping couples and families reach agreements without going through the court process. This study uses a qualitative approach with a case study method, involving observation and in-depth interviews with community leaders, couples involved, and families. The study results indicate that community leaders have a significant success in mediating polygamy cases using personal and religious approaches that are by local values. The effectiveness of this non-litigation mediation is determined by community trust in the integrity of the leader, a good understanding of legal and religious aspects, and communication skills used in conflict resolution. However, the challenges faced include differences of opinion between couples and families, as well as the limited authority of community leaders in making binding decisions. In conclusion, the role of community leaders in non-litigation mediation of polygamy cases in Parakan District has proven effective in reducing domestic conflict, although it requires further support and cooperation from various parties to ensure the sustainability and continuity of the mediation results. Keywords:  : Community Leaders, Non-Litigation Mediation,  Polygamy